2021
DOI: 10.14218/jcth.2020.00188
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Resection Versus Stereotactic Body Radiation Therapy Plus Transhepatic Arterial Chemoembolization for Large Hepatocellular Carcinoma: A Propensity Score Analysis

Abstract: Background and Aims:There are no comparative studies on the efficacy of hepatic resection (HR) and CyberKnife stereotactic body radiation therapy (CK-SBRT) plus transhepatic arterial chemotherapy embolization (TACE) in the treatment of large hepatocellular carcinoma (HCC). Therefore, this study aimed to compare the efficacy of HR and CK-SBRT+TACE in large HCC. Methods: A total of one hundred and sixteen patients were selected from November 2011 to December 2016. Among them, 50 were allocated to the CK-SBRT+TAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Several studies have confirmed that advanced HCC patients can benefit from liver resection ( 16 , 28 , 29 ), but these studies rarely focus on PS1 alone. In the present study, AFP, tumor size and albumin were identified as independent prognostic factors, which was consistent with previous studies and indicated high heterogeneity in such patients ( 30 32 ). It is necessary to further stratify HCC patients of PS1 alone according to these factors to identify appropriate candidates for liver resection.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have confirmed that advanced HCC patients can benefit from liver resection ( 16 , 28 , 29 ), but these studies rarely focus on PS1 alone. In the present study, AFP, tumor size and albumin were identified as independent prognostic factors, which was consistent with previous studies and indicated high heterogeneity in such patients ( 30 32 ). It is necessary to further stratify HCC patients of PS1 alone according to these factors to identify appropriate candidates for liver resection.…”
Section: Discussionsupporting
confidence: 93%
“…With the advancement of technology, RT has become one of the treatment options for localized HCC not suitable for or refractory to conventional treatments. 3 Despite the intraarterial approach by yttrium-90 and increased dose intensity by stereotactic body RT (SBRT), radiotherapeutic effects remain unsatisfactory. 26 The inhibition of radiation-activated signaling pathways to overcome the sublethal effect may be a strategy to enhance the therapeutic effect of RT on hepatic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…2 With the advancement of technology, radiotherapy (RT) has become one of the treatment choices for localized HCC tumor(s) not suitable for the conventional treatments. 3 However, enhancing the therapeutic effect of RT while protecting the surrounding healthy tissue is a great challenge to liver tumors. Hence, specific compounds targeting the inhibition of radiation-activated signaling might meet the requirement.…”
Section: Introductionmentioning
confidence: 99%
“…The plans enclosed PTV with 75–90% isodose line of maximum dose equated to the prescribed dose. Normal tissue tolerance doses were determined according to the AAPM TG-101 report [20] . Doses of 49 to 56 Gy in 5–7 fractions were delivered to the PTV everyday in weekdays for most patients.…”
Section: Methodsmentioning
confidence: 99%